2014
DOI: 10.1128/mcb.00643-14
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Proteasomal Degradation of Posttranscriptional Regulators of the TIS11/Tristetraprolin Family Is Induced by an Intrinsically Unstructured Region Independently of Ubiquitination

Abstract: The TIS11/tristetraprolin (TTP) CCCH tandem zinc finger proteins are major effectors in the destabilization of mRNAs bearing AU-rich elements (ARE) in their 3= untranslated regions. In this report, we demonstrate that the Drosophila melanogaster dTIS11 protein is short-lived due to its rapid ubiquitin-independent degradation by the proteasome. Our data indicate that this mechanism is tightly associated with the intrinsically unstructured, disordered N-and C-terminal domains of the protein. Furthermore, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 78 publications
2
42
0
Order By: Relevance
“…Unexpectedly, ubiquitination of TTP could not be detected, nor was TTP protected from proteasomal degradation by mutation of all five lysine residues [82]. These observations suggest an atypical mode of degradation of TTP protein.…”
Section: Ttp Protein Stability Is Modulated By Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, ubiquitination of TTP could not be detected, nor was TTP protected from proteasomal degradation by mutation of all five lysine residues [82]. These observations suggest an atypical mode of degradation of TTP protein.…”
Section: Ttp Protein Stability Is Modulated By Phosphorylationmentioning
confidence: 99%
“…These observations suggest an atypical mode of degradation of TTP protein. The only 3D structure of TTP protein solved to date is for the highly conserved central zinc finger region [83], and secondary structure prediction programmes all fail to identify any stable structure in the N-terminal and C-terminal domains [82] (JLED, unpublished data). The unstructured nature of the majority of TTP protein is consistent with proteasomal degradation via a default degradation pathway shared with other largely unstructured proteins [84].…”
Section: Ttp Protein Stability Is Modulated By Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex also serves to protect TTP from dephosphorylation in a protein phosphatase 2A (PP2A)-dependent manner (Sun et al, 2007) and prevent degradation of TTP via the proteasome (Deleault et al, 2008;Pfeiffer and Brooks, 2012). There are, however, some data to suggest that the role of 14-3-3 proteins might be limited to chaperoning TTP and only preventing its dephosphorylation (Marchese et al, 2010;Ngoc et al, 2014). The additional role as a block on proteasomal degradation is challenged, as recombinant 14-3-3 in the presence of TTP did not affect TTP stability and degradation by the proteasome (Ngoc et al, 2014).…”
Section: Phosphorylation Of Ttp Proteinmentioning
confidence: 99%
“…There are, however, some data to suggest that the role of 14-3-3 proteins might be limited to chaperoning TTP and only preventing its dephosphorylation (Marchese et al, 2010;Ngoc et al, 2014). The additional role as a block on proteasomal degradation is challenged, as recombinant 14-3-3 in the presence of TTP did not affect TTP stability and degradation by the proteasome (Ngoc et al, 2014). This is in line with data that showed that TTP levels increased when cells were in the presence of a proteasome inhibitor.…”
Section: Phosphorylation Of Ttp Proteinmentioning
confidence: 99%